Extractive in situ product removal for the application of naturally produced l-alanine as an amine donor in enzymatic metaraminol production. Issue 13 (22nd June 2021) - Mack, Kevin; Doeker, Moritz; Grabowski, Laura; Jupke, Andreas; Rother, Dörte
Abstract : The efficiency of the enzymatic metaraminol production with the amine donor l -alanine was increased two-fold by applying extractive in situ product removal. Abstract : Vicinal amino alcohols such as metaraminol find direct application in pharmaceuticals and serve as building blocks for fine chemicals. The amine transaminase enzyme can facilitate the stereoselective production of such amino alcohols, which have two chiral centers, e.g. by transamination from 2-hydroxy ketones in the presence of an amine donor. The feasibility of enzymatic metaraminol production has already been demonstrated with the amine donor isopropylamine. This amine donor has the drawback of an unfavorable reaction equilibrium for the target reaction and being crude oil-based. Therefore, we substituted isopropylamine with the bio-based amine donor l -alanine. As the transamination reaction is also thermodynamically limited when utilizing l -alanine, in situ liquid–liquid extraction of metaraminol can solve this drawback and was implemented to increase the conversions and initiate downstream processing steps. We investigated a suitable solvent–enzyme combination and determined a distinct operational window in terms of reaction conditions for combining the enzymatic metaraminol production with product extraction in a smart process concept. This study thus presents a powerful example for the use of the bio-based amine donor l -alanine in combination with efficient process intensification of biocatalytic drug synthesis by means of in situ product removal.